The growth performance and nutrient digestibility of pigs fed rain tree (Albizia saman) pods as a replacement for maize - Irekhore Oluwakemi T.; Akinsoyinu Akintunde O.; Bello Kazeem O. (Journal of Agricultural Sciences (Belgrade), 2022)
The growth performance and nutrient digestibility of pigs fed diets containing rain tree pods (RPs) were evaluated using 20 pigs. Five diets were formulated with RP replacing maize in the control diet at 10, 20, 30 and 40%. The pigs were randomly allotted to the 5 dietary treatments, with 4 replicates of one (1) pig per replicate, and fed ad libitum for eight weeks. Data were collected on initial weight, final weight (FW), daily feed intake (DFI), daily weight gain (DWG), feed conversion ratio (FCR), cost per kilogram feed (CKF), and feed cost per kilogram weight gain. At week eight, the pigs were moved into individual metabolic crates for a digestibility trial. Rain tree pods, feed and fecal samples were analyzed for proximate composition, and metabolic energy was calculated following standard procedures. The apparent digestibility of dry matter, crude protein, ether extract, ash, and nitrogen-free extract were calculated. Data generated were analyzed using a one-way analysis of variance. The growth performance of pigs fed a 10% RP diet was similar to those fed a control diet. As the dietary inclusion of RP increased, the DFI, DWG and FW of the pigs decreased (p<0.001). The FCR increased while CKF reduced significantly (p<0.001) with an increasing level of RP in the diets. Apparent nutrient digestibility was depressed (p<0.01) with the inclusion of RP in the diets of pigs. This study concluded that the inclusion of 10% RP as a replacement for maize in the diet of growing pigs gave optimal growth performance and reduced feed cost.